The effect of credit risk and liquidity risk on profitability in state-owned banks listed on the Indonesia Stock Exchange 2017-2024 - Sintya Aprilia; RR Dimas Veronica P; Tati Herlina; Rosmala Dewi; Hasiatul Aini (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes the effect of credit risk and liquidity risk on profitability in state-owned banks listed on the Indonesia Stock Exchange over the 2017–2024 period. Credit risk is proxied by Non-Performing Loans (NPL), liquidity risk is measured using the Loan to Deposit Ratio (LDR), and profitability is represented by Return on Assets (ROA). Employing a quantitative research design, the study applies panel data regression analysis that combines cross-sectional and time-series data to capture both firm-specific and temporal effects. The findings indicate that, partially, credit risk has a negative and significant effect on profitability, suggesting that higher levels of non-performing loans reduce banking performance. In contrast, liquidity risk shows a positive and significant effect on profitability, indicating that better liquidity management contributes to improved financial returns in state-owned banks. Simultaneously, both credit risk and liquidity risk significantly influence profitability, confirming their joint importance in determining bank performance. The coefficient of determination reveals that these variables explain approximately 25.07% of profitability variation, while the remainder is influenced by other unobserved factors. These results highlight that profitability in state-owned banks is shaped by a combination of risk management practices and other internal and external determinants. The study emphasizes the importance of maintaining effective credit risk control and balanced liquidity management to support sustainable banking performance, while also suggesting that future research incorporate additional financial and macroeconomic variables to better explain profitability dynamics in the banking sector. Keywords: Credit Risk; Liquidity Risk; Profitability; Non-Performing Loans; Loan to Deposit Ratio; Return On Assets